THE CONCEPTION OF LIVING AS THE CONSISTUENT OF EASTERNCHRISTIAN STUDIES: WORD-VIEW EDUCATIONAL ASPECT - Martych, Ryslana V. (Educological discourse, 2016)
The degree of investigation of the problem is analized in the article, the attention is concentrated on those researches of eastern patristics, in which the comprehension of living “is interweaved” in its theological outline . It is mentioned that during the IX-XIV century the translations of men of God’s inheritance and the attempts of its interpretation has been obtaining considerable extension. Afterwards in research literature the eastern patristics is considered as a phase in the development of the history of philosophy besides that, the conception of living has been becoming the foundation of understanding of God, the correlation of spirit soul and body, cosmology. It is indicated that the comprehension of peculiarities of living by easternchristian thinkers became possible due to the conceptualization of the problems of the christian dogma in the field of ontology, gnoseology, anthropology.Fundamentally important is the idea of comprehension of created “existing” due to which the researches came to the problem of “living” (but only as the manifestation of hypostasis), distinguishing the “living” in hypostasis expression as a being and sensible living in hypostasical expression as a person. It is established in the subdivision that in the in the soviet study the question of eastern patristics on the whole and the essence of living in particular were traditionally considered in the context of the history of philosophy from the position of the influence of ancient tradition on the compositions of some separate church fathers or some separate periods of the christaian philosophy ‘s development and the estetical thought of late antiquity and early medievalism. Ideologically directed approach to the theology appeared on the researches of easternchurches studies in soviet ; some activation of the explanation of the theoretical inheritance of church fathers were monitored only in the 80-th years of the XXth century. Orthodox researches elaborate this thematic actively in the emigration (L.Karsavin, A.Kartashov, archimandrite Kiprian (Kern) and others.).In the article the attention is consentrated on the interpretation of conceptions “creating” and “birth” as to the Son of God, that has made impossible the division of the “living” on self-existing and nonself-existing and became the precondition of the determination of the hierarchy of living (G.Florovskyi). The attention is concentrated on the comprehension of the problem of “living” by earlychristian thinkers in the aspect of distinguishing of its content as forming beginning trhough the established internal relations between the spiritual beings (Losskyi), also the question of descent and the essence of living in correlation with the spiritual word of the person is examined.(bishop Vasyliy (Rodzyanko)).